2010
DOI: 10.1093/molehr/gaq100
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional expression of type-I interferon response genes and stability of housekeeping genes in the human endometrium and endometriosis

Abstract: Endometriosis is a painful chronic female disease defined by the presence of endometrial tissue implants in ectopic (Ec) locations. The pathogenesis is much debated, and type-I interferons (IFNs) could be involved. The expression of genes of the type-I IFN response were profiled by a specific PCR array of RNA obtained from Ec and eutopic (Eu) endometrium collected from nine endometriosis patients and nine healthy control women. Transcriptional expression levels of selected IFN-regulated and housekeeping genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…Our present study confirmed that ECs expresses less miR-126 than EUs, further validating the results of previous miRNA profiling studies of EMs [25,[32][33][34]. The present study may provide initial evidence that miR-126 may participate [35,36]. However, previous studies indicated that the differential expression profiles of miRNA in EMs might play an incipient role in aberrant gene expression in endometrium, priming it to become a new target of investigation [25,[31][32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…Our present study confirmed that ECs expresses less miR-126 than EUs, further validating the results of previous miRNA profiling studies of EMs [25,[32][33][34]. The present study may provide initial evidence that miR-126 may participate [35,36]. However, previous studies indicated that the differential expression profiles of miRNA in EMs might play an incipient role in aberrant gene expression in endometrium, priming it to become a new target of investigation [25,[31][32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…The possible involvement of type I IFNs in endometriosis has recently been investigated directly (Vestergaard et al, 2011). A type I interferon-specific PCR Array indicated significantly down-regulated transcription of the genes HOXB2 and ISG20 in endometriosis lesions compared with endometrium from endometriosis patients and healthy controls, but no difference in the expression of any other interferon stimulated genes were observed.…”
Section: Type I Interferon and Endometriosismentioning
confidence: 99%
“…The transcriptional expression of ISG20 (interferon-stimulated gene product of 20 kDa, also called HEM45) was shown by validated qRT-PCR to be highly down-regulated in endometriosis lesions (Vestergaard et al, 2011). ISG20 transcription is induced synergistically by type I and II IFNs, induced by estrogen, and regulated in a progesteronedependent manner in mice, especially in the mouse endometrium.…”
Section: The Isg20 Proteinmentioning
confidence: 99%
See 2 more Smart Citations